An Australian approach to the policy translation of deliberated citizen perspectives on biobanking - Molster, C.; Maxwell, Susannah; Youngs, L.; Potts, A.; Kyne, G.; Hope, F.; Dawkins, Hugh; O'Leary, Peter (S. Karger AG, 2012)
Background: Deliberative public engagement is recommendedfor policy development in contested ethical areas.Scholars provide little guidance on how deliberative outputscan be translated to policy. This paper describes the processeswe undertook to design a deliberative public forum forcitizens to develop recommendations on biobanking thatwere adopted as health policy. Method: The 4-day forum,held in 2008 in Perth, Western Australia, was designed in collaborationwith academic experts. Deliberant recommendationswere recorded in a formal report presented to policymakers.Deliberations were audio-taped and transcribed.Translation involved transcript analyses, comparison of recommendationsto other stakeholder views and post-forumconsultations. Results: Sixteen citizens made recommendationson ethical, legal and social issues related to biobanking.Most recommendations were translated into biobankingguidelines, with which Western Australia government healthagencies must comply. The value of deliberative public participationin policy-making was most evident when tradeoffsin competing interests, hopes and concerns were required. Translation issues included the impact of a smallnumber of participants with limited socio-demographic diversityon procedural and policy legitimacy. Conclusions:Assessing the sufficiency of diversity in citizen representationwas central to the deliberation-to-translation process.Institutional context facilitated the uptake of deliberationand translation processes. The use of these processes influencedpolicy substance and credibility among stakeholdersand contributed to the state government directive that policycompliance be mandatory. We urge others to publish deliberation-to-translation processes so that best-practicesmay be identified.